2022
DOI: 10.1002/app.52116
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polycaprolactone on physicochemical, biological, and mechanical properties of polyethylene oxide and polyamino acids nano block copolymers

Abstract: This work aims to design robust and biocompatible nano blockcopolymers (NBCPs) of polycaprolactone@-polyethylene oxide-polyaminoacid (PCL@-PEO-PAAs) by ring-opening polymerization. Mechanical behavior including modulus, elongation at yield and break of the tetra block copolymer are studied at room temperature. The significant result lies when the extension

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…It is also studied that the spherical necklace rings are interconnected to each other by several chemical bonding which depends on external parameters such as sonication time, solvent, staining chemicals, and so on. 27 Figure 3a-d and the insets of Figure 3c, d represent very interesting morphology for PEO-b-PAAs-b-PNI-PAM@PCL NBCPs. This polymer looks like a petunia bell-shaped flower-like structure at lower magnification.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…It is also studied that the spherical necklace rings are interconnected to each other by several chemical bonding which depends on external parameters such as sonication time, solvent, staining chemicals, and so on. 27 Figure 3a-d and the insets of Figure 3c, d represent very interesting morphology for PEO-b-PAAs-b-PNI-PAM@PCL NBCPs. This polymer looks like a petunia bell-shaped flower-like structure at lower magnification.…”
Section: Resultsmentioning
confidence: 93%
“…The reason can be explained by the involvement of thermally stable PCL in the latter case. 27 However, a shifted onset of degradation to higher temperatures and an additional bump is observed for PEO-b-PAAs-b-PNIPAM NBCPs due to the absence of PCL in it. It is also observed that former NBCPs lost 76% of their mass while the latter NBCPs lost 84% at 450 C. hence these NBCPs can be utilized up to 340 C for biomedical applications or tissue engineering purposes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations